Direct determination of Helicobacter pylori vacA genotypes and cagA gene in gastric biopsies and relationship to gastrointestinal diseases - Rudi, Jochen; Rudy, Andreas; Maiwald, Matthias; Kuck, Dirk; Sieg, Andreas; Stremmel, Wolfgang (The American journal of gastroenterology, 1999)
Our aim was to detect Helicobacter pylori (H. pylori) from gastric biopsies of 248 patients using a novel, polymerase chain reaction (PCR)-based methodology, which simultaneously facilitates the determination of H. pylori vacA genotypes and cagA gene.